Investigation of the structure activity relationship of flufenamic acid derivatives at the human TRESK channel K2P18.1. Issue 20 (15th October 2016) - Monteillier, Aymeric; Loucif, Alexandre; Omoto, Kiyoyuki; Stevens, Edward B.; Vicente, Sergio L.; Saintot, Pierre-Philippe; Cao, Lishuang; Pryde, David C.
Graphical abstract: Abstract: TRESK (Twik RElated Spinal cord K + channel) is a member of the Twin Pore Domain potassium channel (K2P) family responsible for regulating neuronal excitability in dorsal root ganglion (DRG) and trigeminal (TG) neurons, peripheral neurons involved in pain transmission. As channel opening causes an outward K + current responsible for cell hyperpolarisation, TRESK represents a potentially interesting target for pain treatment. However, as no crystal structure exists for this protein, the mechanisms involved in the opening action of its ligands are still poorly understood, making the development of new potent and selective openers challenging. In this work we present a structure activity relationship (SAR) of the known TRESK opener flufenamic acid (FFA) and some derivatives, investigating the functional effects of chemical modifications to build a TRESK homology model to support the biological results. A plausible binding mode is proposed, providing the first predictive hypothesis of a human TRESK opener binding site.